Exploring barriers to accessing health care services by young women in rural settings: a qualitative study in Australia, Canada, and Sweden - Reyhaneh Golestani; Farideh Khalajabadi Farahani; Paul Peters (BMC Public Health)
Abstract Background The aim of this study is to explore young rural women’s perceived barriers in accessing healthcare services with a focus on the interrelation between three marginalization criteria: age (youth), gender (female), and place of residence (rural areas) in Australia, Canada, and Sweden. Methods Using a qualitative interpretive approach, we conducted semi-structured in-depth interviews with 31 young women aged 18 to 24 in selected rural communities. Data collection took place from May 2019 to January 2021, and the qualitative data were analyzed using NVivo software. Results Self-perceived barriers for access to healthcare services among young women living in rural and remote areas encompass various challenges across individual, institutional, and structural levels. Individual barriers include limited knowledge about available health services, negative attitudes toward healthcare, psychological discomfort when seeking assistance, and economic affordability issues. Institutional challenges involve limited healthcare resources, gender insensitivity among providers, judgmental attitudes from healthcare staff, inadequate time management of services, and a lack of privacy and confidentiality within facilities. Structural barriers further compound these issues through socio-cultural and gender norms, insufficient coverage of universal health insurance, low budget allocations for health facilities in rural and small urban areas, and the geographic distance to healthcare providers. Addressing these multifaceted barriers is crucial to improving healthcare access for rural population. Conclusions Appropriate strategies and policies must be introduced to promote access to healthcare services in rural and remote areas even in most high-`income countries.